Conceptions and misconceptions about neuroscience in preschool teachers: a study from Argentina - Hermida, Maria Julia (2016)
Background: Teachers’ conceptions and misconceptions about neuroscience are crucial in establishing a proper dialogue between neuroscience and education. In recent years, studies in different countries have examined primary and secondary school teachers’ conceptions. However, although preschool education has proved its importance to later academic outcomes, there is limited investigation of neuroscience conceptions focused exclusively on preschool teachers. Purpose: The present study sought to explore preschool teachers’ conceptions and misconceptions about neuroscience in an Argentine setting. Sample, design and methods: We used quantitative and qualitative approaches to explore concepts about neuroscience, including specific neuromyths. Data were collected using a 24-statement questionnaire and 5 in-depth interviews. The survey was administered to 204 teachers of children between the ages of 0–5-years in Argentina. Results and conclusions: Results from this exploratory study suggested a relatively high level of general knowledge of neuroscience amongst the preschool teachers in the study. However, three particular issues seemed unclear for teachers: memory, plasticity and the myth that ‘we only use 10% of the brain’. Specifically, ‘memory’ was understood as ‘learning by heart’; neural underpinnings of memory and plasticity processes were unknown; and the myth that we only use 10% of the brain was used to explain individual differences in intelligence in a straightforward way. In addition, anecdotal evidence was used by teachers to justify their conceptions about neuroscience. Finally, the wider implications of these results for bridging neuroscience and education are discussed.